Modulation of the lncRNA TCONS_00265853-miR-421-5p-CLOCK axis by Ziyin Buyang Formula in polycystic ovarian syndrome with circadian rhythm disruption: an integrated bioinformatics and experimental approach - Huang, Haixia; Sun, Ling; Jia, Fan; Tan, Yong; Zhou, Yahong (Frontiers in Genetics, 2025)
BackgroundPolycystic ovarian syndrome (PCOS), a common endocrine disorder in reproductive-aged women, is linked to circadian rhythm disruption, but the molecular mechanisms remain unclear. Dysregulation of the lncRNA TCONS_00265853-miR-421-5p-CLOCK axis may play an important role. Ziyin Buyang Formula (ZYBYF), a Traditional Chinese Medicine (TCM) targeting kidney Yin-Yang balance, shows therapeutic potential, though its mechanism is unclear. This study explores ZYBYF’s role in modulating this axis to improve circadian-disrupted PCOS.MethodsNetwork pharmacology identified ZYBYF’s bioactive components and targets, integrated with PCOS-associated genes and circadian disruption-related differentially expressed genes (DEGs) from ovarian tissues. A continuous light-induced PCOS rat model (10-week 24-h light exposure) was employed to validate ZYBYF’s effects. Interventions included ZYBYF treatment.ResultsBioinformatics identified 25 intersection targets, with MAPK signaling as the central pathway. In vivo, circadian disruption downregulated lncRNA TCONS_00265853 and CLOCK, elevated miR-421-5p, and hyperactivated MAPK (p-p38, p-ERK1/2, p-JNK), exacerbating ovarian apoptosis (↑BAX, ↓Bcl-2, p < 0.001). ZYBYF restored circadian axis components (↑TCONS_00265853, CLOCK; ↓miR-421-5p), suppressed MAPK activation, and normalized ovarian morphology and hormonal profiles (↓LH, T, ACTH; ↑E2, FSH, p < 0.001). PRKCA expression, a MAPK regulator, was rescued by ZYBYF, counteracting dysregulation of IL1B, VEGFA, and TGFB1.ConclusionCircadian disruption exacerbates PCOS via the TCONS_00265853-miR-421-5p-CLOCK axis, driving MAPK hyperactivation and ovarian apoptosis. ZYBYF reverses these effects, restoring hormonal balance and follicular dynamics. This study provides mechanistic validation of ZYBYF’s efficacy, positioning it as a promising therapeutic strategy for circadian-disrupted PCOS. These findings suggest that ZYBYF may modulate circadian rhythm–related pathways in PCOS via the lncRNA–miRNA–CLOCK axis, warranting further mechanistic validation.